THE IMPACT OF INCLUSIVE LEADERSHIP BEHAVIORS ON WORK PASSION: AN ANALYTICAL STUDY OF THE PERCEPTIONS OF A SAMPLE OF TEACHING STAFF AT TIKRIT UNIVERSITY (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Research Objectives: The current research aimed to identify the impact of inclusive leadership behaviors on work passion, through an analytical study of the opinions of a sample of teaching staff at Tikrit University.Research Methodology: The research adopted the (descriptive analytical method), which is characterized by the great flexibility it provides, as it enables the diagnosis and study of reality in a more accurate manner.Data Collection Tools: The questionnaire was used as the main tool for collecting data and information related to the researched sample.Research Population and Sample: The research population consisted of teaching staff from all colleges at Tikrit University, numbering (3119) members. A purposive sample of (342) teaching staff was taken.Statistical Tools Used: The statistical programs (SPSS V.23) and (AMOS V.20) were adopted to conduct statistical analysis, using methods such as arithmetic mean, standard deviation, Pearson correlation coefficient, and T-test, F-test.Most Important Results: The results of the analytical study show that inclusive leadership behaviors have a positive and direct effect on work passion among teaching staff.
Keywords: Inclusive Leadership Behaviors, Work Passion, Harmonious Passion, Obsessive Passion, Teaching Staff at Tikrit University.